A New Edible Film to Produce In Vitro Meat - Nicole Orellana (Foods, 2020)
In vitro meat is a novel concept of food science and biotechnology. Methods to produce in vitro meat employ muscle cells cultivated on a scaffold in a serum-free medium using a bioreactor. The microstructure of the scaffold is a key factor, because muscle cells must be oriented to generate parallel alignments of fibers. This work aimed to develop a new scaffold (microstructured film) to grow muscle fibers. The microstructured edible films were made using micromolding technology. A micromold was tailor-made using a laser cutting machine to obtain parallel fibers with a diameter in the range of 70−90 µm. Edible films were made by means of solvent casting using non-mammalian biopolymers. Myoblasts were cultured on flat and microstructured films at three cell densities. Cells on the microstructured films grew with a muscle fiber morphology, but in the case of using the flat film, they only produced unorganized cell proliferation. Myogenic markers were assessed using quantitative polymerase chain reaction. After 14 days, the expression of desmin, myogenin, and myosin heavy chain were significantly higher in microstructured films compared to the flat films. The formation of fiber morphology and the high expression of myogenic markers indicated that a microstructured edible film can be used for the production of in vitro meat.